2004
DOI: 10.1002/jmv.20105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a total hepatitis C virus (HCV) core antigen assay for the detection of antigenaemia in anti‐HCV positive individuals

Abstract: A new, sensitive enzyme immunoassay has been developed for detecting and quantifying total hepatitis C virus (HCV) core antigen in anti-HCV positive or negative sera ("trak-C", Ortho Clinical Diagnostics, Raritan, NJ). The purpose of this study was to evaluate the performance of trak-C as an additional laboratory diagnostic marker of viraemia. The performance was compared to HCV-RNA detection in the "screening" of sera from a large heterogeneous population of hospitalised patients and outpatients. Six hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…To the best of our knowledge, five studies evaluated the usefulness of HCV core antigen as a marker of active/ongoing HCV infection in the therapynaïve patients [Cano et al, 2003;Agha et al, 2004;Krajden et al, 2004;Netski et al, 2004;Valcavi et al, 2004]. These studies reported on HCV RNA positive samples from 114 to 348 and showed the OTCA to be 86.9-97.4% as sensitive as NAT.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To the best of our knowledge, five studies evaluated the usefulness of HCV core antigen as a marker of active/ongoing HCV infection in the therapynaïve patients [Cano et al, 2003;Agha et al, 2004;Krajden et al, 2004;Netski et al, 2004;Valcavi et al, 2004]. These studies reported on HCV RNA positive samples from 114 to 348 and showed the OTCA to be 86.9-97.4% as sensitive as NAT.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the detection in the present study of one sample that was ''RNA negative/core antigen positive'' (Table I) might be explained if the detection of HCV core antigen and RNA were correlated to the detection of hepatitis B e antigen (HBeAg) and hepatitis B DNA. In this instance, not all the HBeAg positive patients may express high levels of HBV DNA and conversely, the absence of HBeAg may not indicate the absence of infectivity [Valcavi et al, 2004]. Further work is required to understand the full dynamics and relationships of these two HCV markers.…”
Section: Discussionmentioning
confidence: 97%
“…Qualitative and quantitative ELISA kit (Ortho-Clinical Diagnostics, Johnson & Johnson Company) have been successively developed for assessment of HCV core antigen and commercially available out of China, such as in Thailand and Italy, to detect HCV core antigen [19,20] . A number of reports have suggested that these assays could be used to reduce the serological preseroconversion window period, measure HCV replication, and monitor the response to antiviral therapy [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…As previously published (1), the testing for the presence of anti-HCV antibody is still recommended for the initial identification of HCV infection in the general population. In anti-HCV EIA-positive subjects, the HCV core Ag assay and other serological tools, such as RIBA and ALT level testing (19), will contribute to establishing the diagnosis of an ongoing HCV infection.…”
Section: Discussionmentioning
confidence: 99%